2013
DOI: 10.1063/1.4819346
|View full text |Cite
|
Sign up to set email alerts
|

Study of vortex-shedding-induced vibration of a flexible splitter plate behind a cylinder

Abstract: A computational analysis of vortex-shedding-induced vibration of a flexible splitter plate behind a cylinder at a low Reynolds number is conducted to understand effects of the length and flexibility of a splitter plate on the drag and lift of a cylinder and vibration of the attached plate. The drag and lift coefficients, the Strouhal number of vortex shedding, and the magnitude of tip displacements of a flexible splitter plate are found to be intricate functions of the plate flexibility. The deflection shape o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…They showed that the oscillation frequency of the plate varies linearly with dilatational wave speed inside the plate (or its natural oscillation frequencies). Lee and You [16] showed that the plate length influences vibration modes of the splitter plate, and the plate displacement is a function of the Young's Modulus and its natural frequencies. Furquan and Mittal [18] investigated flow past two sideby-side square cylinders with flexible splitter plates and observed lock-in for the plate frequency closer to its first natural frequency.…”
Section: Studies On Steady/pulsatile Inflow Past Flexible Thin Structmentioning
confidence: 99%
“…They showed that the oscillation frequency of the plate varies linearly with dilatational wave speed inside the plate (or its natural oscillation frequencies). Lee and You [16] showed that the plate length influences vibration modes of the splitter plate, and the plate displacement is a function of the Young's Modulus and its natural frequencies. Furquan and Mittal [18] investigated flow past two sideby-side square cylinders with flexible splitter plates and observed lock-in for the plate frequency closer to its first natural frequency.…”
Section: Studies On Steady/pulsatile Inflow Past Flexible Thin Structmentioning
confidence: 99%
“…In this benchmark, an elastic plate attached to the lee side of a rigid cylinder develops self-sustained oscillation in 2D laminar channel flow. The FSI studies of flexible thin structures by Dunne and Rannacher [9], Heil et al [10], Bhardwaj and Mittal [11], Lee and You [12] and Tian et al [13] showed validation of their respective solvers against the benchmark proposed by Turek and Hron [8].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we provide benchmark results which will serve as validation data for FSI solvers coupled with convective heat transfer. Since several previous numerical studies [9,10,11,12,13] used FSI benchmark proposed by Turek and Hron [8] to validate FSI solvers, we propose an extension of this FSI benchmark to account for coupled convective heat transfer in the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…Laminar flow past a circular cylinder with a thin flexible tail is a popular two-dimensional numerical benchmark for FSI solvers. The benchmark configuration was first proposed in Turek and Hron [2006], and has since been adopted by many researchers to validate different FSI solvers (e.g., Heil et al [2008], Kollmannsberger et al [2009], Bhardwaj and Mittal [2012], Lee and You [2013] among others). Three different test cases -based on the fluid velocity at the inlet and the material parameters of the deformable tail -were proposed in the original paper of Turek and Hron [2006].…”
Section: Flow Past a Circular Cylinder With Flexible Tailmentioning
confidence: 99%